Organizational Culture and Its Impact in Determining the Strategic Orientation: An Empirical Study of the Ministry of Higher Education and Scientific Research of Iraq - Mustafa, Khalidiya; Abbas, Same; Ahmed, Hameed (The Arab Journal of Administration, 2019)
Attention to the concept of organizational culture has increased as one of the important and influential regulatory changes in the organization’s performance on the part in determining the strategic orientation of its other side, the aim of the research disclosure of the impact of the elements of organizational culture and of )organizational values, organizational beliefs, regulatory expectations, regulatory norms( in deter- mine the strategic orientation elements of )pre-emptive, defensive, analytical, response( in the Office of the Ministry of Higher Education and scientific research to achieve the objectives of the research raised several questions and hypotheses were tested based on the statistical programs ready )spss ver-20( of the arithme- tic mean and standard deviation and coefficient of rank correlation )spearman( to measure the nature of the relationship between research laboratories and linear regression variables )linear regression( to measure the impact of credit relations questionnaire as a tool for measuring by ) 6( in charge of graduate-level ad- ministrative leaders. The importance of research sponsored by rooting intellectual of the nature of search variables based on the applied voltage through the application of theoretical concepts in the scientific field, the highlights were the findings of the research results show a positive correlation and significant effect between organizational culture and strategic orientation. This indicates that the organizational culture of the role an important and active in shaping the strategic orientation of the Ministry of Education. The major recommendations represented the need for a comprehensive survey of the ministry to the needs of uni- versities and related institutions and constantly improve the level of output in line with the labor market after conducting surveys and analysis of the surrounding environment ,And to direct the attention of the higher departments in the Ministry of Higher Education and Scientific Research to the need to consolidate the concept of organizational culture, especially expectations and organizational values of its importance in determining the strategic direction of the ministry.